Case report From Diabetes to Neuropathy: A Diagnostic Journey to Leigh Syndrome - Behzadi, Arya; poormehr, pooya; Saneifard, hedyeh; Shakiba, Marjan (Iranian Journal of Child Neurology, 2025)
Diabetes is one of the most common chronic disorders in the world, characterized by chronic hyperglycemia. Among the rare causes of diabetes, Leigh syndrome is a rare genetic mitochondrial disorder with unusual manifestations like neurological deficits in addition to typical diabetes symptoms. This report enlightens others about the unusual presentation of diabetes in a pediatric population. The studied case is a 6-year-old girl with hypothyroidism and diabetes. Post-SARS-CoV-2 infection, she developed progressive lower limb weakness. Magnetic resonance imaging (MRI) and electromyography-nerve conduction velocity (EMG-NCV) revealed brain lesions and polyneuropathy. Genetic testing using whole exome and Sanger sequencing confirmed mitochondrial gene mutations in the MT-NDI location, diagnosing her with Leigh syndrome. Pediatric diabetic patients typically present with Type 1 diabetes mellitus (T1DM) or Type 2 diabetes mellitus (T2DM), but other causes must be considered. Leigh syndrome can manifest with neurological symptoms, requiring clinicians to recognize its diverse presentations for proper management. This case highlights the importance of considering rare etiologies for diabetes to improve the prognosis and quality of life.